Handbook of transatlantic North American studies - Straub, Julia (Handbooks of English and American studies, 2016)
Transatlantic literary studies have provided important new perspectives on North American, British and Irish literature. They have led to a revision of literary history and the idea of a national literature. They have changed the perception of the Anglo-American literary market and its many processes of transatlantic production, distribution, reception and criticism. Rather than dwelling on comparisons or engaging with the notion of ‘influence,’ transatlantic literary studies seek to understand North American, British and Irish literature as linked with each other by virtue of multi-layered historical and cultural ties and pay special attention to the many refractions and mutual interferences that have characterized these traditions since colonial times. This handbook brings together articles that summarize some of the crucial transatlantic concepts, debates and topics. The contributions contained in this volume examine periods in literary and cultural history, literary movements, individual authors as well as genres from a transatlantic perspective, combining theoretical insight with textual analysis.